Studi Kasus Yayasan X: Analisa Hasil Exit Questionnaire Survey - Santosa, Bernadetta Junita (Humaniora, 2011)
This case study on the X Foundation aims to provide an overview and analysis of questionnaire results of exit interviews of employees who came out in 2009 and 2010. This case study was conducted on the basis of the importance of seeing the dimensions or factors that exist, particularly with regard to the factors of satisfaction or dissatisfaction in the employee working within the Organization. The study was conducted using quantitative methods with retrieval of primary data on the X Foundation, the descriptive method. Subjects were 63 employees who came out in 2009 and 125 employees that came out in 2010 at differing position, level and status. The results generally showed that there are two factors that should motivate employees to be the opposite that is causing dissatisfaction in the employee, and there are two factors also confirm the reasons why an employee becomes dissatisfied and decided to leave the organization. The suggestions put forward to conduct further research to further deepen the analysis of descriptive statistics, so the depiction becomes more profound; and can provide accurate advice to the organization.